Al-IslÄm wa al-Pancasila fÄ« Dawâ€™i KifÄh Nahdlatul Ulama (NU) - Haidar, Ali (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Since the adoption of Pancasila as the sole basis for any socio-political organization (orsospol) and community organizations (CBOs) by the government, the debate about the relationship between Islam and the state of Indonesia, especially between Islam and Pancasila, is considered complete. At least there is no Islamic group that openly contradicting Islam with Pancasila. Even acceptance of Pancasila as the sole foundation Indonesian nation and state has been regarded by some as the final decision.DOI:Â 10.15408/sdi.v1i3.850